Students’ Perceptions of Vocabulary Learning Strategies in Enhancing Word Recognition at MTs Negeri 2 Kota Palu - Basiradanuwijaya, Trisnawaty (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Vocabulary recognition is a fundamental skill in learning English as a foreign language (EFL), especially at the junior high school level. This study aimed to explore students’ perceptions of vocabulary learning strategies in enhancing English vocabulary recognition among eighth grade students at MTs Negeri 2 Kota Palu. The research employed a qualitative descriptive design. The participants were ten eighth grade students selected through purposive sampling. Data were collected through semi-structured interviews to gain in-depth information about the strategies students use and their perceptions of these strategies. The data were analyzed using thematic analysis by identifying, coding, and categorizing emerging themes. The findings revealed that students used various vocabulary learning strategies, including repetition, note-taking, dictionary use, guessing meaning from context, and simple digital tools. Among these strategies, repetition and writing new words were the most frequently used because students considered them easy and practical. Overall, students showed positive perceptions toward vocabulary learning strategies. They believed that consistent practice helped them recognize English words more quickly and understand meanings more clearly in reading activities. However, some challenges were identified, such as boredom in memorizing word lists and distraction when using digital devices. The study concludes that vocabulary learning strategies play an important role in improving students’ vocabulary recognition. Explicit instruction and regular practice of appropriate strategies are recommended to support students’ vocabulary development and enhance their English learning outcomes.